Criminología cultural. Las peleas de gallos en Monterrey. De lo rural a lo urbano - Velázquez Rojas, Martín (Archivos de criminología, seguridad privada y criminalística, 2020)
From a qualitative approach, the essay constitutes historical research on the origin and meaning of cockfighting in Monterrey during the 20th century. Its roots are investigated in great civilizations and its roots in novohispana society until this tradition, usually underground, surfaced in some communities of the northern sector of Monterrey, Cienega de Flores, as well as in the Old Town of San Nicolas de los Garza that make up the universe of study. Methodologicalally, documentary research was conducted in local archives and combined with fieldwork seeking ethnographic interpretation. The author concludes that cockfights are inscribed in forms of subaltern culture that first settle on the peripheries, on the margins of the city, to travel towards the strictly urban. From the underworld of underground mechanisms of socialization are being established between the Galleria and their audiences, between the solusers and the punters, profiling a culture that survives to this day in certain areas of the metropolitan area of Monterrey.